HIV/AIDS: MANAGEMENT AND STIGMA - Frizelle, Kerry (PINS-Psychology in Society, 2025)
Deacon, H with Stepheny, D & Prosalendis, S (2005) Understanding HIV/AIDS stigma: A theoretical and methodological analysis. Cape Town: HSRC Press. ISBN 0 7969 2104 0 pbk. Pages 120. Vass, J & Phakathi, S (2006) Managing HIV in the workplace: Learning from SMEs. Cape Town: HSRC Press. ISBN 0 7969 2161 X pbk. Pages 108. In the course of offering HIV/AIDS training I have had the opportunity to work with two particularly interesting groups of individuals; the first group included a number of artists, and the second a number of trainee farmers. On both occasions I was asked to cover the basic facts about HIV/AIDS and to discuss and debate possible ways in which each group could respond to the challenges of the virus within their areas of work. This proved to be a difficult task. While a few artists may group themselves into small businesses, many of them come together periodically for commissioned work (disbanding when the project is over) or are self-employed. The farmers, on the other hand, manage groups of workers, many of whom are contract workers and a relatively transient group. In preparing for this work I found it difficult to access relevant literature and information on how these individuals could respond to the epidemic. While there is a large body of literature on the impact of the virus on large companies and a number of existing HIV/AIDS programmes and services that have been designed around the needs (and budgets) of large companies, there is very little that deals with the impact and management of HIV/AIDS on, and in small businesses and even less on how the virus impacts on the informal sector and how this can be prevented and managed. The HSRC monograph Managing HIV in the workplace: Learning from SMEs is therefore a welcome, but long overdue, addition to the body of research and literature on HIV/AIDS in the workplace.